(untitled) (International Journal of Engineering and Computer Science, 2018)
This proposed work is an attempt to design and implement advanced and robust vehicle security system using GPS and GSM system to prevent robbery and to analyze the exact location of vehicle. The safety of the vehicle is very significant. This project is designed using GPS and GSM technology and accelerometer. The system contains GPS module, GSM modem, Infrared sensors, DTMF tone decoder, ARM 7 microcontroller, relay switch and accelerometer.GPS system tracks the location of vehicle, GSM system is used for duplex communication. The preventive measures like fuel supply cutoff, engine ignition cutoff electric shock system (installed on steering wheel) and paint spray system are installed in the vehicle which is controlled by user GSM Mobile. Traffic accidents are one of the leading causes of deaths. An important indicator of survival after an accident is the time between the accident and emergency medical personnel dispatched to the accident spot. By reducing the time between an accident occurrence and dispatch of the responders to the scène, mortality rates can be reduced, thereby we can save lives. In this project, the main application is early accident detection and its notification to the concerned emergency Centre. By using accelerometer accident notification can be achieved. Accelerometer can automatically detect traffic accident and immediately notify to central emergency centre, by using GPS co-ordinates we can reach to the location and rescue one’s life. This complete system is designed taking into consideration low range vehicles to provide extreme security to their vehicles and life.